Anti-fatigue effect of traditional Chinese medicines: A review - Weimei Yu; Chengzhu Song; Zi Lei; Yanjuan Li; Xudong He; Jie Yu; Xingxin Yang (Elsevier, 2023)
A third of the world's population suffers from unexplained fatigue, hugely impacting work learning, efficiency, and health. The fatigue development may be a concomitant state of a disease or the side effect of a drug, or muscle fatigue induced by intense exercise. However, there are no authoritative guides or clinical medication recommendations for various fatigue classifications. Traditional Chinese medicines (TCM) are used as dietary supplements or healthcare products with specific anti-fatigue effects. Thus, TCM may be a potential treatment for fatigue. In this review, we outline the pathogenesis of fatigue, awareness of fatigue in Chinese and western medicine, pharmacodynamics mechanism, and substances. Additionally, we offer a comprehensive summary of fatigue and forecast the potential effect of novel herbal-based medicines against fatigue.